War and Escalation in South Asia - Peters, John E. (RAND Corporation, 2006)
This monograph highlights key factors in South Asia imperiling U.S. interests, and suggests how and where the U.S. military might play an expanded, influential role. It suggests seven steps the military might take to better advance and defend U.S. interests in South Asia, the Middle East, and Asia at large. Washington should intensify involvement in South Asia and become more influential with the governments there. Given the area's potential for violence, it should also shape part of the U.S. military to meet potential crises.